2021
DOI: 10.1007/s00464-020-08246-4
|View full text |Cite
|
Sign up to set email alerts
|

IMHOTEP: cross-professional evaluation of a three-dimensional virtual reality system for interactive surgical operation planning, tumor board discussion and immersive training for complex liver surgery in a head-mounted display

Abstract: Background Virtual reality (VR) with head-mounted displays (HMD) may improve medical training and patient care by improving display and integration of different types of information. The aim of this study was to evaluate among different healthcare professions the potential of an interactive and immersive VR environment for liver surgery that integrates all relevant patient data from different sources needed for planning and training of procedures. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Also, medical education and specialized HPB apprentices may profit from immersive virtual reality applications due to the interactive use and the possibility to interact with multiple participants and over distances. This is in concordance with recent literature that evaluated a similar VR application to be suited mostly for student and resident training [17]. To date, this is the main development goal of the presented application.…”
Section: Discussionsupporting
confidence: 87%
“…Also, medical education and specialized HPB apprentices may profit from immersive virtual reality applications due to the interactive use and the possibility to interact with multiple participants and over distances. This is in concordance with recent literature that evaluated a similar VR application to be suited mostly for student and resident training [17]. To date, this is the main development goal of the presented application.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 85%
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Cartucho et al 13 compared 2D images and 3D models displayed by a wearable mixed-reality device and reported that the 3D models were more highly evaluated by the surgeons. As surgeons with less surgical experience evaluated 3D models more highly than experienced surgeons, 10,14 we speculate that less experienced surgeons with lower spatial awareness may benefit more from 3D models. The surgeons in this study had 20 and 32 years of surgical experience.…”
Section: Discussionmentioning
confidence: 97%